(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The environment at limiting factors in the Southern coast of the Crimea determine intensity of thymol biosynthesis in essential oil of Thymus vulgaris L., Th. pulegioides L. and Th. striatus Vahl. other during period. The model of ecological and genetic control thymol biosynthesis in essential oil Thymus L. is appied to the basic ontogeny phases.